USING THE LIE CATEGORY IN THE SPEECH OF MEDICAL PERSONNEL - Nargiza Kurbanova (International Scientific and Current Research Conferences, 2023)
The use of the category of lies in the speech of medical personnel in the conversation between the doctor and the patient and the delivery of diagnosis results to the patient and the improvement of health and the patient's realistic view of life, the importance of the role of speech, and the importance of speech culture are incomparable. In linguistics, research was conducted on the theory of speech art in various languages, including foreign scientists such as J. Bentham, A. Judis, S. P. Foley, M. M. Hinks, E. Grinko, and in Uzbek linguistics, Sh. Zokirkho'jaev , scientists such as A.H. Aripova, E. Kasimov, I. Miylieva, D. Teshabaeva, H. Rasulov conducted research on the topic of public speaking. The relevance of this scientific article lies in the fact that the use and characteristics of the false category in the speech of English and Uzbek medical workers have not been studied in a cross-sectional aspect. This article covers the following: the use of the lying category between the patient in communication was explained in English and Uzbek in a mixed aspect; specific characteristics of the culture of interaction between medical staff and patients are revealed; the importance of language tools expressing the meaning of praise and respect in the speech communication model of medical staff is proven;